2021
DOI: 10.3389/fimmu.2021.653489
|View full text |Cite
|
Sign up to set email alerts
|

Germline Genetic Variants of Viral Entry and Innate Immunity May Influence Susceptibility to SARS-CoV-2 Infection: Toward a Polygenic Risk Score for Risk Stratification

Abstract: The ongoing COVID-19 pandemic caused by the novel coronavirus, SARS-CoV-2 has affected all aspects of human society with a special focus on healthcare. Although older patients with preexisting chronic illnesses are more prone to develop severe complications, younger, healthy individuals might also exhibit serious manifestations. Previous studies directed to detect genetic susceptibility factors for earlier epidemics have provided evidence of certain protective variations. Following SARS-CoV-2 exposure, viral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 218 publications
0
19
0
1
Order By: Relevance
“…Recent studies have identified deleterious variants involved in IFN type I signaling, including variants of TLR-3; transcription factors, such as STAT1 and STAT2; interferon regulatory factors, such as IRF1 and IRF7; and IFN-α receptors, such as IFNAR1 e IFNAR2, are associated with inadequate immune responses after vaccination as well as the most severe cases of COVID-19. This is reflected at the cellular level, where pDCs cannot produce IFNs during SARS-CoV-2 infections [16,185]. In another work, TLR-3, IRF3, and IRF7 variants were detected in patients with severe COVID-19.…”
Section: Polymorphisms In Tlr and Their Signaling Moleculesmentioning
confidence: 95%
See 4 more Smart Citations
“…Recent studies have identified deleterious variants involved in IFN type I signaling, including variants of TLR-3; transcription factors, such as STAT1 and STAT2; interferon regulatory factors, such as IRF1 and IRF7; and IFN-α receptors, such as IFNAR1 e IFNAR2, are associated with inadequate immune responses after vaccination as well as the most severe cases of COVID-19. This is reflected at the cellular level, where pDCs cannot produce IFNs during SARS-CoV-2 infections [16,185]. In another work, TLR-3, IRF3, and IRF7 variants were detected in patients with severe COVID-19.…”
Section: Polymorphisms In Tlr and Their Signaling Moleculesmentioning
confidence: 95%
“…More particularly, TLR-7 and TLR-8 recognize single-stranded RNA (ssRNA), while intermediate RNA (double-stranded RNA or dsRNA) produced during viral replication is detected by TLR-3 [179][180][181]. TLR signal transduction implicates myeloid differentiation factor 88 (MyD88) and TIR domain-containing adaptor-inducing interferon-beta (TRIF), activating NF-kB, type I IFN regulatory factor (IRF)3, and IRF7, leading to a type I IFN response [16,182].…”
Section: Polymorphisms In Tlr and Their Signaling Moleculesmentioning
confidence: 99%
See 3 more Smart Citations